La capacitación docente en educación sexual para la prevención del embarazo adolescente en bachillerato general unificado - Merelo Moncayo, Oquendo Honorato (2021)
The objective of the research presented in this document is to analyze teacher training in matters of sexual education for the prevention of pregnancy in adolescents in the unified general high school of the Samborondón Fiscal Education Unit. Where it is detected that the students do not have basic information on the prevention of pregnancy, nor the risks of contracting sexually transmitted diseases. The inquiry is based on a mixed approach, because it allowed the statistical analysis of objective reality and to verify the idea to defend about teacher training in sex education prevents pregnancy in adolescents from the educational institution. ………